Applied drama and theatre as an interdisciplinary field in the context of HIV/AIDS in Africa - Barnes, Hazel, 1953- (Rodopi, 2013)
Drama for Life, University of the Witwatersrand, aims "to enhance the capacity of young people, theatre practitioners and their communities to take responsibility for the quality of their lives in the context of HIV and AIDS in Africa. We achieve this through participatory and experiential drama and theatre that is appropriate to current social realities but draws on the rich Indigenous knowledge of African communities."Collected here is a representative set of research essays written to facilitate dialogue across disciplines on the role of drama and theatre in HIV/AIDS education, prevention,
Keywords: Drama -- Therapeutic use.; HIV infections -- Africa.; Manners and customs.; Health promotion.; Africa, Sub-Saharan.; HIV Infections -- psychology; Psychodrama; Cultural Characteristics; Health Knowledge, Attitudes, Practice; Health Promotion; Africa South of the Sahara; Infections à VIH -- Afrique.; Psychodrame.; Mœurs et coutumes.; Promotion de la santé.; Afrique subsaharienne.; customs (social concepts); HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Diseases.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Manners and customs; Health promotion; Drama -- Therapeutic use; HIV infections; Sub-Saharan Africa; Africa; Aids -- Motiv; Therapeutisches Theater; Subsaharisches Afrika